2007
DOI: 10.1021/ja0739943
|View full text |Cite
|
Sign up to set email alerts
|

Resistive-Pulse Studies of Proteins and Protein/Antibody Complexes Using a Conical Nanotube Sensor

Abstract: There is increasing interest in using nanopores in synthetic membranes as resistive-pulse sensors for molecular and macromolecule analytes. In general, this method entails measuring current pulses associated with translocation of the analyte through the nanopore sensor element. A key challenge for this sensing paradigm is building selectivity into the protocol so that the current pulses for the target analyte can be distinguished from current pulses for other species that might be present in the sample. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
237
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(245 citation statements)
references
References 67 publications
7
237
0
1
Order By: Relevance
“…The fully electrical molecular detection is also unique compared with technologies such as Biacore, a surface plasmon resonancebased bioanalyzer (28), in that it works without optical signal readout. For such electrical detection, a nanoporous structure is known to be suitable, especially when it is used in resistive-pulse mode (29,30). In this study we showed another practical option using functionalized glass nanopipettes in which antibodies of interest were immobilized on the surface of individual nanopipettes rather than dispersed in the bulk solution.…”
Section: Discussionmentioning
confidence: 96%
“…The fully electrical molecular detection is also unique compared with technologies such as Biacore, a surface plasmon resonancebased bioanalyzer (28), in that it works without optical signal readout. For such electrical detection, a nanoporous structure is known to be suitable, especially when it is used in resistive-pulse mode (29,30). In this study we showed another practical option using functionalized glass nanopipettes in which antibodies of interest were immobilized on the surface of individual nanopipettes rather than dispersed in the bulk solution.…”
Section: Discussionmentioning
confidence: 96%
“…For example, if a receptor is immobilized to the nanopore surface, then the presence of the target will cause a change in ion current as long as the target is bound. There is a growing arsenal of techniques for chemically modifying the surface of nanopores (Nguyen et al, 2011, Sexton, et al, 2007, Wanunu&Meller, 2007. There is nothing about this particular sensing mechanism that requires nanoscale pores.…”
Section: Ion Current Modulation Methodsmentioning
confidence: 99%
“…These applications require no labelling of the protein, which can sometimes change binding properties. For example, the Martin group has shown that the electrical signature of a protein can be distinguished from that of the protein bound to an antibody fragment (Sexton et al, 2007). In that report, tracketched nanopores were coated with gold to make a conical nanotube of tip opening 9 to 27 nm in diameter.…”
Section: Resistive-pulse Sensingmentioning
confidence: 99%
“…But even covalent bonding can be used for attachment if appropriate functional groups exist on the etched surface. This is a starting point for biospecific single-channel sensors [51][52][53][54][55][56][57][58][59][60].…”
Section: Asymmetric Single Poresmentioning
confidence: 99%